2018
DOI: 10.4238/gmr16039916
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Genetic expression of pobA and fabHB in Bacillus licheniformis M2-7 in the presence of benzo[a]pyrene

Abstract: Bacillus licheniformis M2-7 is a heat-resistant bacterium able to biotransform polycyclic aromatic hydrocarbons. It can transform a wide range of these compounds as naphthalene, phenanthrene, pyrene and benzo[a]pyrene. Benzo[a]pyrene is a polycyclic aromatic hydrocarbon of high molecular weight considered as potentially toxic and carcinogenic for humans. Aiming to discover the genes involved in the biotransformation of benzo[a]pyrene, we made a B. licheniformis M2-7 genomic library in E. coli. We isolated two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…En B. licheniformis M2-7, se propuso una vía de transformación de BaP, de acuerdo con los resultados reportados recientemente por nuestro grupo (Guevara-Luna et al, 2018) y junto con la identificación y el análisis de expresión de los genes catE, pobA y fabHB (Rojas-Aparicio et al, 2018). Las reacciones comenzarían con la incorporación de oxígeno molecular en los carbonos 9 y 10 del BaP a través de la enzima catecol 2, 3-dioxigenasa, generando el benzo[a]pireno cis-9,10-dihidrodiol (Guevara-Luna et al, 2018), este último metabolito sufre otra dioxigenación a través de la catecol 2,3-dioxigenasa produciendo el ácido cis-4-(hidroxipireno-8-il)-2-oxobut-3-enoico vía meta (Schneider et al, 1996).…”
Section: Discussionunclassified
“…En B. licheniformis M2-7, se propuso una vía de transformación de BaP, de acuerdo con los resultados reportados recientemente por nuestro grupo (Guevara-Luna et al, 2018) y junto con la identificación y el análisis de expresión de los genes catE, pobA y fabHB (Rojas-Aparicio et al, 2018). Las reacciones comenzarían con la incorporación de oxígeno molecular en los carbonos 9 y 10 del BaP a través de la enzima catecol 2, 3-dioxigenasa, generando el benzo[a]pireno cis-9,10-dihidrodiol (Guevara-Luna et al, 2018), este último metabolito sufre otra dioxigenación a través de la catecol 2,3-dioxigenasa produciendo el ácido cis-4-(hidroxipireno-8-il)-2-oxobut-3-enoico vía meta (Schneider et al, 1996).…”
Section: Discussionunclassified
“…In our knowledge, this is the first evidence about the role of csrA expression under a recalcitrant contaminant. Rojas-Aparicio et al [20] reported that B. licheniformis M2-7 in the presence of polycyclic aromatic hydrocarbons increases the expression of the catE, pobA and fabHB genes, whose products are proteins related to the metabolism of hydrocarbons [20], therefore, the Csr system could be regulating growth on gasoline by controlling the expression of these genes. In this study, we also evaluated the role of CsrA on motility of B. licheniformis.…”
Section: Discussionmentioning
confidence: 99%
“…To quantify the level of expression of the csrA and hag genes, the extraction and purification of the total RNA of the strain of Bacillus licheniformis M2-7 and LYA-5 were carried out, following the protocol described by Rojas-Aparicio et al [20] with some modifications. The contaminating residual DNA was treated with DNase I (Thermo Scientific, USA) and the RNA was stored at -70℃.…”
Section: Expression Of the Csra And Hag Genes By Real Time Pcrmentioning
confidence: 99%
“…Bacillus licheniformis M2-7 es una bacteria anaerobia facultativa y termorresistente, con un rango de temperatura de crecimiento de 37 a 60°C y puede resistir temperaturas de 110°C (Guavara-Luna et al, 2022). Se ha demostrado que B. licheniformis M2-7 utiliza hidrocarburos como gasolina y gasóleo, como única fuente de carbono (Guavara-Luna et al, 2022), también puede crecer en presencia de Hidrocarburos Aromáticos Policíclicos (HAPs), como naftaleno, fenantreno, pireno y benzo [a]pireno (Guavara-Luna et al, 2018;Rojas-Aparicio et al, 2018) y se ha reportado que esta cepa utiliza el Sistema Regulador de Almacenamiento de Carbono (Csr, por sus siglas en inglés) como mecanismo para degradar hidrocarburos (Serrano-Ángel et al, 2020;Blancas et al, 2023). El sistema Csr es un regulador global de diversos procesos celulares (Vakulskas et al, 2015), en varias especies de bacterias Gramnegativas (Lawhon et al, 2003), es un complejo de unión al ARN que se encarga de regular la expresión génica a nivel postranscripcional, afectando la unión al ribosoma y/o a la estabilidad de los ARNm blancos (Yakhnin et al, 2007;Edwards et al, 2011).…”
Section: Introductionunclassified